PENGARUH ELECTRONIC WORD OF MOUTH DAN PERSEPSI NILAI TERHADAP KEPUTUSAN PEMBELIAN PADA SITUS LAZADA - Trinik Susmonowati; Husnul Khotimah (JURNAL LENTERA BISNIS, 2021)
As technology develops, people begin to change their lifestyle in shopping transactions that previously had to go out of home to buy necessities, nowadays only need gadgets that have internet networks to shop through online markets. This study aims to determine the effect of Electronic Word of Mouth and perceived value on purchasing decisions on Lazada. The population in this research is all North Jakarta people who have made a purchase through the Lazada with total sample 150 respondent. The data collection techniques in this study were nonprobability sampling techniques with accidental sampling techniques. This study used a quantitative approach and questionnaires as a primary data. Testing the hypothesis in this study using a single linear regression and multiple linear regression using software spss 24. The results showed that there was a positive and significant effect between electronic word of mouth regarding purchasing decisions on Lazada. There is a positive and significant effect between perceived values of purchasing decisions on Lazada. And together there is a positive and significant effect between electronic word of mouth and perceived value of purchasing decisions on the Lazada at 53.9% while the remaining 46.1% is determined by other variables not included in this study.Keyword: Electronic Word of Mouth, Perceived Value, Purchasing Decisions.